1981
DOI: 10.1192/bjp.138.6.479
|View full text |Cite
|
Sign up to set email alerts
|

Some Electrophysiological Observations in Obsessional States

Abstract: Averaged evoked potentials were recorded from a group of obsessional patients and matched normal controls for three types of visual stimulation: passive monitoring of a light flash, a pattern consisting of gratings and a cognitive task involving discrimination of two similar shapes. As the complexity of information processing required by the tasks increased, differences in the evoked potentials of obsessionals became more marked. The main finding was of faster latency and reduced amplitude of the N220 componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 12 publications
3
32
0
Order By: Relevance
“…Johannes and collaborators (1997) observed a target P300 amplitude reduction in groups characterized as «pure» GTS, but who actually showed a clinical profile very similar to our GTS+OCS group. Similar results were previously obtained with pure OCD groups (Beech et al, 1983;Ciesielski et al, 1981;Malloy et al, 1989;Sanz et al, 2001;Towey et al, 1994). Nonetheless, these earlier studies didn't mention the relationship between P300 component and symptom intensity.…”
Section: Influence Of Obsessive-compulsive Symptoms On Erp Profilesupporting
confidence: 78%
“…Johannes and collaborators (1997) observed a target P300 amplitude reduction in groups characterized as «pure» GTS, but who actually showed a clinical profile very similar to our GTS+OCS group. Similar results were previously obtained with pure OCD groups (Beech et al, 1983;Ciesielski et al, 1981;Malloy et al, 1989;Sanz et al, 2001;Towey et al, 1994). Nonetheless, these earlier studies didn't mention the relationship between P300 component and symptom intensity.…”
Section: Influence Of Obsessive-compulsive Symptoms On Erp Profilesupporting
confidence: 78%
“…Moreover, if information processing has a tendency toward more controlled processing modes, shorter information-processing times and shorter P300 latency can be expected in anorexia with increasing task complexity as has been shown in obsessive-compulsive disorders (Ciesielski, Beech, & Gordon, 1981;Tower et al, 1990). We therefore set out to test these hypotheses in different experimental conditions by varying stimulus content (body images vs. geometrical shapes) and task complexity (easy vs. difficult).…”
Section: Introductionmentioning
confidence: 95%
“…Flor-Henry et al [1979] reported that OCD patients had frontal-temporal lobe dysfunction of the dominant hemisphere on power spec tral EEG analysis, cognitive impairment on neuropsycho logical test performance and a high prevalence of left-handedness. Ciesielski et al [1981] recorded visualevoked potentials in 8 patients with primary O-C neuro sis and matched controls using three types of visual stim uli. They found that O-C patients had significantly shorter latencies and a reduced amplitude of the N220 component in response to a complex grating pattern and cognitive task but not a simple light Hash.…”
Section: Biological Evidencementioning
confidence: 99%